The Integrals in Gradshteyn and Ryzhik. Part 7: Elementary examples - Amdeberhan, Tewodros; Moll, Victor H. (Scientia Series A: Mathematical Sciences, 2025)
The table of Gradshteyn and Ryzhik contains some elementary integrals. Some of them are derived here.
Keywords: elementary integrals